A CIE Color Purity Algorithm to Detect Black and Odorous Water in Urban Rivers Using High-Resolution Multispectral Remote Sensing Images - Shen, Qian; Yao, Yue; Li, Junsheng; Zhang, Fangfang; Wang, Shenglei; Wu, Yanhong; Ye, Huping; Zhang, Bing (IEEE transactions on geoscience and remote sensing, 2019)
Urban black and odorous water (BOW) is a serious global environmental problem. Since these waters are often narrow rivers or small ponds, the detection of BOW waters using traditional satellite data and algorithms is limited both by a lack of spatial resolution and by imperfect retrieval algorithms. In this paper, we used the Chinese high-resolution remote sensing satellite Gaofen-2 (GF-2, 0.8 m). The atmospheric correction showed that the mean absolute percentage error of the derived remote sensing reflectance ( R_{\mathrm {rs}} ) in visible bands is 25.19%. We first measured R_{\mathrm {rs}} spectra of two classes of BOW [BOW with high concentrations of iron (II) sulfide, i.e., BOW1 and BOW with high concentrations of total suspended matter, i.e., BOW2] and ordinary water in Shenyang. Then, in situ R_{\mathrm {rs}} data were converted into R_{\mathrm {rs}} corresponding to the wide GF-2 bands using the spectral response functions. We used the converted R_{\mathrm {rs}} data to calculate several band combinations, including the baseline height, [ R_{\mathrm {rs}} (green) - R_{\mathrm {rs}} (red))/( R_{\mathrm {rs}} (green) + R_{\mathrm {rs}} (red)], and the color purity on a Commission Internationale de L'Eclairage (CIE) chromaticity diagram. The color purity was found to be the best index to extract BOW from ordinary water. Then, R_{\mathrm {rs}} (645) was applied to categorize BOW into BOW1 and BOW2. We applied the algorithm to two synchronous GF-2 images. The recognition accuracy of BOW2 and ordinary water are both 100%. The extracted river water type near Weishanhu Road was BOW1, which agreed well with ground truth. The algorithm was further applied to other GF-2 data for Shenyang and Beijing.